Age structure of owned dogs under compulsory culling in a visceral leishmaniasis endemic area - Bortoletto, Danielly Vieira [UNESP]; Utsunomiya, Yuri Tani [UNESP]; Venturoli Perri, Silvia Helena [UNESP]; Ferreira, Fernando; Nunes, Caris Maroni [UNESP] (Cadernos Saude Publica, 2016)
The age structure of the dog population is essential for planning and evaluating control programs for zoonotic diseases. We analyzed data of an owned-dog census in order to characterize, for the first time, the structure of a dog population under compulsory culling in a visceral leishmaniasis endemic area (Panorama, Sao Paulo State, Brazil) that recorded a dog-culling rate of 28% in the year of the study. Data on 1,329 households and 1,671 owned dogs revealed an owned dog: human ratio of 1: 7. The mean age of dogs was estimated at 1.73 years; the age pyramid indicated high birth and mortality rates at the first year of age with an estimated cumulative mortality of 78% at the third year of age and expected life span of 2.75 years. In spite of the high mortality, a growth projection simulation suggested that the population has potential to grow in a logarithmic scale over the years. The estimated parameters can be further applied in models to maximize the impact and minimize financial inputs of visceral leishmaniasis control measures.
Keywords: Dogs; Age Distribution; Visceral Leishmaniasis; Zoonoses